INSECTICIDE-TOLERANT BACTERIAL POPULATION IN Eisenia fetida’s GUT AND VERMICAST EXPOSED TO CHLORANTRANILIPROLE AND FIPRONIL (Applied Biological Research, 2023)
An experiment was conducted to evaluate the impact of chlorantraniliprole  and fipronil on the bacterial population of gut of Eisenia fetida and its  vermicast. Thirty adult earthworms were exposed to chlorantraniliproleand fipronil-treated cow dung in 30 L capacity tub. Enumeration was done by spread plate technique and the bacteria were identified on the basis of  morpho-biochemical characteristics. Studies revealed that E.  fetida survived even after the exposure to high concentration of  chlorantraniliprole and fipronil, perhaps due to the presence of tolerant  bacteria in the earthworm’s gut. The chlorantraniliprole and fipronil  largely affected the bacterial population in earthworm’s gut and its  vermicast. Chlorantraniliprole proved more harmful than fipronil.  Maximum reduction in total viable tolerant bacterial colonies in earthworm  gut and vermicast was 2.42 and 2.95%, respectively, when exposed to the  mixed concentration of chlorantra-niliprole and fipronil (5.00 and 8.34 mg kg-1, respectively). Overall, the vermicast had more tolerant bacterial  colonies than the gut of E. fetida.
Keywords: Chlorantraniliprole; Eisenia fetida; fipronil; tolerant bacterial colonies; vermicast